1999
DOI: 10.1074/jbc.274.48.34253
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Selectivity Is a Determinant of RGS2 Function

Abstract: RGS (regulator of G protein signaling) proteins areGTPase-activating proteins that attenuate signaling by heterotrimeric G proteins. Whether the biological functions of RGS proteins are governed by quantitative differences in GTPase-activating protein activity toward various classes of G␣ subunits and how G protein selectivity is achieved by differences in RGS protein structure are largely unknown. Here we provide evidence indicating that the function of RGS2 is determined in part by differences in potency tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
149
2
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(167 citation statements)
references
References 36 publications
12
149
2
4
Order By: Relevance
“…M1 mAChR is functionally linked to G q/11 ␣, and we have shown previously that RGS2 selectively interacts with G q ␣ (31,33,34). Initially our studies did not distinguish whether the RGS-G␣ interaction could occur while RGS2 is bound to M1i3, or whether the RGS protein was released prior to it actions on G␣.…”
Section: Differential Binding Profiles Of Various Rgs Proteins With Tmentioning
confidence: 78%
“…M1 mAChR is functionally linked to G q/11 ␣, and we have shown previously that RGS2 selectively interacts with G q ␣ (31,33,34). Initially our studies did not distinguish whether the RGS-G␣ interaction could occur while RGS2 is bound to M1i3, or whether the RGS protein was released prior to it actions on G␣.…”
Section: Differential Binding Profiles Of Various Rgs Proteins With Tmentioning
confidence: 78%
“…It is known that RGS2 localizes to the mammalian cell plasma membrane more efficiently than other R4/B subfamily members and also functions as a more potent inhibitor of muscarinic receptor G␣ q signaling (15)(16)(17). However, the relative contribution of three previously reported membrane targeting mechanisms to its localization and receptor inhibition has not been determined.…”
mentioning
confidence: 79%
“…Plasma Membrane Targeting Is a More Important Functional Determinant than Intrinsic RGS-box Function-Previous data from our laboratory showed that RGS2 contained three unique amino acid residues in its RGS-box domain that mediate its selective inhibition of G␣ q -versus G␣ i -mediated signaling (15). To determine whether G␣ q selectivity could explain the enhanced relative function of RGS2, we compared the ability of the RGS-box domains of RGS2 and RGS5 to act as inhibitors of M1 muscarinic receptor signaling.…”
Section: Rgs2 Is a More Potent Inhibitor Of M1 Muscarinic Receptormedmentioning
confidence: 99%
See 1 more Smart Citation
“…Axin contacts with the APC peptide are green (52). Residues in RGS2 that, when converted to their equivalents in RGS4, enhance GAP activity toward G␣ i (74) are indigo. Mutations in p115RhoGEF that decrease G␣ 13 GAP activity are hot pink (53).…”
Section: Fig 1 Protein Binding Surfaces Of Rh Domainsmentioning
confidence: 99%